Janus kinase inhibitors in palmoplantar pustulosis: a mixed-methods feasibility (JAKPPPOT) trial protocol - Weiyu Ye; Suzie Cro; James B Galloway; Sarah Chapman; C H Smith; Kingsley Powell; Jonathan Barker; Ann Naylor; Helen McAteer; John Gregory; David Gleeson; April Qin; et al. (BMJ Open)
Background Palmoplantar pustulosis (PPP) is a rare, debilitating inflammatory skin disease involving painful pustules on the palms and soles. Janus kinase (JAK) inhibitors target pathways relevant to PPP disease biology but also confer a risk of major adverse cardiovascular events and malignancy in certain ‘at risk’ individuals; this includes those with PPP given prevalent smoking and cardiovascular risk factors in the PPP population. The feasibility of JAK inhibitor therapy for PPP requires assessment prior to a randomised controlled trial evaluation of drug efficacy and safety for this indication.Methods and analysis The ‘Janus kinase inhibitors in palmoplantar pustulosis: a mixed-methods feasibility’ trial is an open-label, single-centre, single-arm, mixed-methods feasibility trial of JAK inhibition in PPP (REC reference: 24/NE/0147; ISRCTN61751241). Participants (n=20) will receive 8 weeks of treatment with the JAK inhibitor upadacitinib (‘Rinvoq’, 30 mg, once daily). Qualitative semistructured interviews (up to n=40) will be undertaken with trial participants, trial decliners and healthcare professionals. The primary outcome will be a composite assessment of feasibility across three domains: recruitment, adherence and acceptability, using a mixed-methods analysis approach. Secondary objectives include the identification of trial recruitment optimisation strategies, using the ‘Quintet Recruitment Intervention’, and the generation of an indication of effect size on disease severity (measured using the Palmoplantar Pustulosis Psoriasis Area and Severity Index) to inform future sample size calculations. Historic placebo control data from the Anakinra for Pustular Psoriasis: Response in a Controlled Trial (National Institute of Health and Social Care reference: 13/50/17; Research Ethics Commitee reference: 16/LO/0436) will be used as the effect size comparator. Study recruitment will be undertaken over a 24-month period, commencing in November 2024.Ethics and dissemination This study has been approved by the Newcastle North Tyneside 2 Research Ethics Committee, 24/NE/0132. Our findings will inform the feasibility of a future adequately powered RCT evaluating the efficacy of JAK inhibitor therapy in PPP.Trial registration number ISRCTN61751241.